PENGEMBANGAN INSTRUMEN UJI KOMPETENSI PEDAGOGICAL CONTENT KNOWLEDGE (PCK) BAGI GURU IPA SMP - Ayunda, Tari Rezky; Natalina L, Mariani; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study is a descriptive study that aims to produce an instrument Pedagogical Content Knowledge competency test for junior high school science teacher. This research was conducted in FKIP Biology, University of Riau and MGMP IPA SMP Pekanbaru in September 2016 until February 2017. This study is Research and Development which used ADDIE model (Analyze, Design, Develop, Implement and Evaluate) and only done to Develop stage. Data was collected by the validation and testing. Validation aims to see usefullness a matter of expert opinion in the field of Pedagogical Content Knowledge IPA SMP, while the trial function to see usefullness the instrument for target users by analyzing the test results. Data obtained from the analysis of the test results in the form of value reliability, level of difficulty, diferentiation capacity and the function of detractors matter. Then, product produced after the validation and test are multiple choice questions with five possible answers which consists of 96 questions with 44 questions Content Knowledge, 36 about Pedagogical Knowledge and Pedagogical Content Knowledge 16. The results showed that the competency test instruments Pedagogical Content Knowledge can be categorized as good and can be used to measure mastery of Pedagogical Content Knowledge junior high school science teacher.Keywords: Instruments, Pedagogical Content Knowledge (PCK), Junior High SchoolScience Teacher